¿Cuándo se interrumpe la prescripción en el ámbito procesal penal? (un nuevo enfrentamiento entre el Tribunal Constitucional y el Tribunal Supremo) - Chozas Alonso, José Manuel (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
According to Article 132.2 of the Spanish Criminal Code, the prescription of crimes and offences is interrupted «as soon as proceedings are directed against the responsible person». Those legal words have been the cause of several interpretative difficulties, as they are too imprecise: it is not legally foreseen which is exactly the concrete moment when it can be understood that the criminal procedure is «directed against the responsible person». Traditionally, Spanish criminal courts (included the Criminal Section of the Spanish Supreme Court) have considered that just filing a suit or a complaint —by the offended subject or by the Prosecution Service— should be sufficient to interrupt crime prescription. However, a recent judgment of the Spanish Constitutional Court (Judgment 63/2005, from 14th March) has retained that it is not enough, because criminal proceedings do not actually begin when the suit or the complaint are filed, but only when the competent criminal court formally opens a criminal procedure. The author tries to reach a solution to this case law confusion, taking a procedural point of view to analyse Article 132.2 of the Criminal Code: «who» and «when» is able to act in order interrupt crime prescription, and «what kind of procedural activity» is therefore needed.